Airport signage as a visual learning medium: evaluating its educational effectiveness in supporting passenger understanding - Nikolas Makanuay; Geby Claudia Tupamahu; Erwin Pasangkin; Rifqi Raza Bunahri (ARKA INSTITUTE, 2026)
Airports function not only as transportation infrastructure but also as non-formal learning environments where passengers interact with visual information systems. Within this context, airport signage can be conceptualized as a visual learning medium that supports incidental learning and facilitates passenger understanding. Grounded in visual learning theory and cognitive processing perspectives, this study aims to evaluate the educational effectiveness of airport signage in supporting passenger understanding at Domine Eduard Osok Airport, Sorong. A qualitative descriptive approach was employed through field observations, documentation, and analysis of relevant regulatory standards. Passenger understanding was interpreted through observable behaviors, including navigation accuracy, hesitation, and reliance on assistance. The findings reveal that several signage elements are not optimally designed or positioned, particularly in terms of visibility, design consistency, and availability in key areas such as check-in and arrivals. These limitations increase cognitive load, hinder information processing, and reduce the effectiveness of signage as a visual learning medium. This study contributes to the field of education by demonstrating how environmental design in public spaces can influence learning processes and user comprehension. The results highlight the need to improve signage quality not only to achieve regulatory compliance but also to enhance its role in supporting non-formal learning and passenger understanding in complex environments.